Self-Efficacy in Indonesian Mathematics Pedagogy: A Systematic Literature Review - Andi Mariani Ramlan; Sri Muliana Ramlan; Farman Farman; Fitri Ramdani (EDUPEDIA PUBLISHER, 2026)
Purpose: This study presents a systematic literature review examining mathematics self-efficacy research within the Indonesian educational context from 2019 to 2024. Methodology: Guided by the PRISMA 2020 protocol, fifty-seven peer-reviewed journal articles were identified through the GARUDA database, meeting strict inclusion and exclusion criteria. Data were analyzed to determine frequently used keywords, primary research themes, and temporal trends. Keyword analysis revealed a predominant focus on constructs such as learning outcomes, problem-solving ability, motivation, and academic achievement, indicating a learner-centered orientation. Findings: Thematic synthesis demonstrated that most studies investigated the impact of self-efficacy on mathematics achievement, with fewer addressing affective factors, conceptual understanding, or higher-order thinking skills. Temporal analysis indicated a publication peak in 2021, followed by a decline, potentially linked to shifts in theoretical frameworks and pandemic-related disruptions. Significance: Findings underscore the critical role of self-efficacy in shaping students’ cognitive, affective, and behavioral engagement in mathematics, and call for more diverse methodological approaches and participant demographics in future research.